Somewhere between Islam and Judaism: critical reflections - Hughes, Aaron W. (Equinox, 2021)
"Somewhere Between Islam and Judaism is of interest to scholars and students of religion concerned with comparison and those studying Islam, Judaism and Jewish-Muslim relations. The essays collected in this volume provide a set of critical reflections on what it means to study these two religious traditions within the larger context of the academic study of religion"--